2012
DOI: 10.1021/ac300189p
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Powder Mixtures by Raman Spectrometry: the influence of particle size and its correction

Abstract: Particle size distribution and compactness have significant confounding effects on Raman signals of powder mixtures, which cannot be effectively modeled or corrected by traditional multivariate linear calibration methods such as partial least-squares (PLS), and therefore greatly deteriorate the predictive abilities of Raman calibration models for powder mixtures. The ability to obtain directly quantitative information from Raman signals of powder mixtures with varying particle size distribution and compactness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Spectral intensities (infrared absorption and Raman intensity) are generally considered proportional to concentration by Boguer-Lambert-Beer Law or by other mathematical formulae derived from the fundamental law of quantitative spectroscopy. [3][4][5][6] However infrared spectra acquired from powdered calcite and other mineral species are known to undergo changes as a function of particle grain size. 2,7-9 The effect of particle size on the spectral resolution of the fundamental vibrations of the [CO3 2-] anion in calcite were identified in infrared emission studies and have been divided into three classes of behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral intensities (infrared absorption and Raman intensity) are generally considered proportional to concentration by Boguer-Lambert-Beer Law or by other mathematical formulae derived from the fundamental law of quantitative spectroscopy. [3][4][5][6] However infrared spectra acquired from powdered calcite and other mineral species are known to undergo changes as a function of particle grain size. 2,7-9 The effect of particle size on the spectral resolution of the fundamental vibrations of the [CO3 2-] anion in calcite were identified in infrared emission studies and have been divided into three classes of behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The scattering properties of the sample can be characterized by a single parameter l* corresponding to the transport length of the light in the medium, also defined as the photon path after which the photon direction is totally randomised23. The penetration depth of the light is therefore proportional to l*.…”
Section: Discussionmentioning
confidence: 99%
“…Defined by unique spectral peak position(s) for each chemical component, Raman scattering provides a basis for qualitative analysis [3] . Meanwhile, the intensity of the unique spectral peak(s) provide basis for quantitative analysis of chemical contaminants in foods [4,5] . Chen et al 2012 reported that particle size influences the quantitative analysis of powder mixtures and used several methods for correction [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the intensity of the unique spectral peak(s) provide basis for quantitative analysis of chemical contaminants in foods [4,5] . Chen et al 2012 reported that particle size influences the quantitative analysis of powder mixtures and used several methods for correction [5] . The authors reported that the correction methods slightly decreased the prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%